2002
DOI: 10.1007/s00122-002-0867-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of microsatellite markers in peach [Prunus persica (L.) Batsch] and their use in genetic diversity analysis in peach and sweet cherry (Prunus avium L.)

Abstract: We report the sequence of 41 primer pairs of microsatellites from a CT-enriched genomic library of the peach cultivar 'Merrill O'Henry'. Ten microsatellite-containing clones had sequences similar to plant coding sequences in databases and could be used as markers for known functions. For microsatellites segregating at least in one of the two Prunus F(2) progenies analyzed, it was possible to demonstrate Mendelian inheritance. Microsatellite polymorphism was evaluated in 27 peach and 21 sweet cherry cultivars. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
295
8
11

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 493 publications
(335 citation statements)
references
References 29 publications
21
295
8
11
Order By: Relevance
“…Farmers continue to maintain these almond accessions and to further exploit the germplasm by traditional planting of seedlings to establish new orchards. The SSR loci used in this study were selected, from a set of primer pairs developed in peach, on the basis of their rate of allelic polymorphism [44][45][46][47][48]. The results obtained in our study are consistent with Sosinski et al [45] and Xie et al [59] data, which confirmed the interspecific usefulness of microsatellite markers in Prunus species.…”
Section: Discussionsupporting
confidence: 88%
“…Farmers continue to maintain these almond accessions and to further exploit the germplasm by traditional planting of seedlings to establish new orchards. The SSR loci used in this study were selected, from a set of primer pairs developed in peach, on the basis of their rate of allelic polymorphism [44][45][46][47][48]. The results obtained in our study are consistent with Sosinski et al [45] and Xie et al [59] data, which confirmed the interspecific usefulness of microsatellite markers in Prunus species.…”
Section: Discussionsupporting
confidence: 88%
“…In both experiments, the markers of choice were the microsatellites. The loci analysed were previously located and developed in peach (Cipriani et al, 1999;Sosinski et al, 2000;Testolin et al, 2000;Dirlewanger et al, 2002), but previous work by Hormaza (2002) demonstrated their suitability for apricot.…”
Section: Introductionmentioning
confidence: 99%
“…file S1) and/or with an inferior quality of amplification pattern. Sixteen markers with clear amplification and the average-above PIC (0.686 ± 0.070), namely EMPaS02, EMPaS05, EMPaS06, EMPaS10, EMPaS11, EMPaS12 (Vaughan and Russell 2004), UCD-CH11, UCD-CH31, UCD-CH12 (Struss et al 2003), UDP97-403, UDP98-411, UDP98-412 (Testolin et al 2000), BPPCT 040, BPPCT 034 (Dirlewanger et al 2002), PS12A02, PceGA34 (Downey and Iezzoni 2000) were identified for further optimization.…”
Section: Resultsmentioning
confidence: 99%